Ethical Leadership and Employee Performance: A Study of Ughelli North and South Local Government Areas of Delta State - AVWERHONYO, Amos; SOKOH, Gbosien Chris (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
This study investigated the impact of ethical leadership on employee performance in Ughelli North and South local government councils of Delta State. The study adopted a cross-sectional research design and a structured survey instrument was used to collect data from a sample of 328 workers randomly selected from Ughelli North and South local government councils. This study was anchor on Leader-Member Exchange (LMX) Theory. The theory hinges on the tenet that leaders cultivate a variety of relationships with their subordinates, ranging from low-quality (out-group) to high-quality (in-group) relationships. The amount of information interchange, trust, competence, dedication, role clarity and work satisfaction are all increased by high-quality LMX. The study four hypotheses were tested at 0.05 levels of significance. Data were analyzed using Statistical Analysis System (SAS 9.2). Pearson correlation coefficient and regression Analysis were used in testing the hypotheses. Findings revealed that ethical leadership (ethical guidance, fairness, role clarification and trust) had positive and significant impact on employee performance. The finding also showed that there was significant relationship between ethical leadership and employee performance in Ughelli North and South local government councils of Delta State. The study concluded that ethical leadership in terms of ethical guidance, fairness, role clarification and trust are imperative for the employees performance in local government councils in Delta State. The recommended among others that local government leader in Delta State should ensure that all employees participate in ethics training programs. This will serve as an opportunity for employees to learn and evaluate the impact of ethical guidance on employee and organizational performance.